Social networking sites addiction and the effect of attitude towards social network advertising - Can, Lutfiye; Kaya, Nihat (Elsevier Science Bv, 2016)
Because of the prevalence of mobile devices, the overuse of social networking sites has become a global phenomenon. Social networking sites (hereafter SNS) give a lot of opportunities for business. First of all, businesses can make advertise their product in an easy way. A lot of SNS users can see companies' advertisements when they use SNS for a different purpose. For marketing management, attitude for advertising is very important. Because Consumers' attitude is an important factor in influencing consumers' purchase intention. Purposes of this study are to (1) identify the effect of habits and perceived ease of use on psychological dependence on SNS; and (2) to explore the relationship between SNS dependence and attitudes toward SNS advertisement. 215 data entries were analyzed through SPSS. Analysis results revealed that social networks have partial impacts on approaches of people who are psychologically bond to these web sites, towards advertisements. (C) 2016 The Authors. Published by Elsevier Ltd.
12th International Strategic Management Conference (ISMC) -- OCT 28-30, 2016 -- Antalya, TURKEY
Keywords: Social media; Social network advertising; Social networking addiction; Attitude